2020
DOI: 10.1177/000313482008600331
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Site-Specific Metastases on Surgical Value and Survival among Metastatic Colorectal Cancer Patients

Abstract: We aimed to explore the potential prognostic impact of the metastatic site on the management approach and prognosis of stage IV colorectal cancer patients with synchronous metastases. Synchronous metastatic colorectal cancer patients reported to the Surveillance, Epidemiology, and End Results Program database between 2010 and 2013 were included in this study. Overall survival (OS) was compared between patients with different treatment options using risk-adjusted Cox proportional hazard regression models. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In addition to the primary site, surgical treatment is another heterogeneous factor. Patients who underwent surgical resection of the primary tumour survived longer than those who did not [ 19 ]. Some studies have shown that resection of lung metastasis also has a positive effect on improving survival outcomes [ 20 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the primary site, surgical treatment is another heterogeneous factor. Patients who underwent surgical resection of the primary tumour survived longer than those who did not [ 19 ]. Some studies have shown that resection of lung metastasis also has a positive effect on improving survival outcomes [ 20 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Lee-Ying et al reported median OS of 42.8 months after LUM compared to 48.0 months after LIM (P=0.69). 12,14,15 Similarly, Iwasaki et al reported estimated 5-year OS of 37.0% after LUM vs 42.8% after LIM (P=0.46). 14 However, Zong et al reported better survival after LUM, with a median OS of 38 months (range 26.5-49.5) after LUM versus 30 months (range 28.0-32.0) after LIM.…”
Section: Lum Is Not Associated With Better Overall Survival Compared To Limmentioning
confidence: 90%
“…The sample sizes in the studies were mostly small, with the exception of Zong et al who studied 1047 patients with CRC LUM. 12 With the exception of Iwasaki et al who published their study in 2005, the publication dates were more recent for the rest of the included sample, ranging from 2015 to 2020.…”
Section: Descriptive Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Surgical metastasectomy (SM) has been performed more frequently for a series of cancer types in the recent decades despite the increasing efficacy of other modern systemic treatment modalities [1–5]. SM improves the overall survival and has become a standard treatment for pulmonary metastases in sarcoma [6] and colorectal liver metastases [7].…”
Section: Introductionmentioning
confidence: 99%